Integration of Mobile Learning into Adult English Teaching in the Digital Age - Zhang, Tao; Saadat, Uranus (Journal of Theory and Practice in Linguistics, 2025)
In the digital age, mobile learning has emerged as a powerful tool for enhancing adult English education. Traditional distance learning methods often face challenges such as limited student engagement, lack of real-time teacher interaction, and difficulties in monitoring learning progress. Mobile learning offers flexibility, accessibility, and personalized learning experiences, allowing adult learners to study anytime and anywhere. By integrating mobile learning into adult English education, instructors can build instant learning platforms, establish teacher-student learning communities, and implement diverse assessment systems. This paper explores the feasibility of mobile learning in adult English teaching, highlighting its potential to improve engagement, foster interactive learning, and accommodate diverse learner needs. The findings suggest that mobile learning can bridge the gaps in traditional distance education, making English learning more effective and accessible for adult learners.